Training: improving antenatal detection and outcomes of congenital heart disease. Issue 4 (24th November 2018) - Uzun, Orhan; Kennedy, Julia; Davies, Colin; Goodwin, Anthony; Thomas, Nerys; Rich, Delyth; Thomas, Andrea; Tucker, David; Beattie, Bryan; Lewis, Michael J
Abstract : Objectives: This study describes the design, delivery and efficacy of a regional fetal cardiac ultrasound training programme. This programme aimed to improve the antenatal detection of congenital heart disease (CHD) and its effect on fetal and postnatal outcomes. Design setting and participants: This was a prospective study that compared antenatal CHD detection rates by professionals from 13 hospitals in Wales before and after engaging in our 'skills development programme'. Existing fetal cardiac practice and perinatal outcomes were continuously audited and progressive targets were set. The work was undertaken by the Welsh Fetal Cardiovascular Network, Antenatal Screening Wales (ASW), a superintendent sonographer and a fetal cardiologist. Interventions: A core professional network was established, engaging all stakeholders (including patients, health boards, specialist commissioners, ASW, ultrasonographers, radiologists, obstetricians, midwives and paediatricians). A cardiac educational lead (midwife, superintendent sonographer, radiologist, obstetrician, or a fetal medicine specialist) was established in each hospital. A new cardiac anomaly screening protocol ('outflow tract view') was created and training on the new protocol was systematically delivered at each centre. Data were prospectively collected and outcomes were continuously audited: locally by the lead fetal cardiologist; regionally by the Congenital Anomaly Register and Information Service in Wales; and nationally by the National Institute for Cardiac Outcomes and Research (NICOR) in the UK. Main outcome measures: Patient satisfaction; improvements in individual sonographer skills, confidence and competency; true positive referral rate; local hospital detection rate; national detection rate of CHD; clinical outcomes of selected cardiac abnormalities; reduction of geographical health inequality; cost efficacy. Results: High levels of patient satisfaction were demonstrated and the professional skill mix in each centre was improved. The confidence and competency of sonographers was enhanced. Each centre demonstrated a reduction in the false-positive referral rate and a significant increase in cardiac anomaly detection rate. According to the latest NICOR data, since implementing the new training programme Wales has sustained its status as UK lead for CHD detection. Health outcomes of children with CHD have improved, especially in cases of transposition of the great arteries (for which no perinatal mortality has been reported since 2008). Standardised care led to reduction of geographical health inequalities with substantial cost saving to the National Health Service due to reduced false-positive referral rates. Our successful model has been adopted by other fetal anomaly screening programmes in the UK. Conclusions: Antenatal cardiac ultrasound mass training programmes can be delivered effectively with minimal impact on finite healthcare resources. Sustainably high CHD detection rates can only be achieved by empowering the regional screening workforce through continuous investment in lifelong learning activities. These should be underpinned by high quality service standards, effective care pathways, and robust clinical governance and audit practices.